Promoting learning management to develop modern learners By designing learning based on multiple intelligences based on 6 dimensions through the SELVES Process. - Autchobkarn, Sutkhanueng; Srithep, Worapol; Shoosit, Prampan (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
In an era of rapidly changing education and learning, the development of learning methods to meet the demands of the modern world is essential. This article introduces a learning management concept through a Six-dimensional Multiple Intelligence-based design to enhance diverse learning in linguistic, kinesthetic, logical, spatial, interpersonal, and naturalistic dimensions through the SELVES Process, which involves: (1) analyzing strengths, (2) creating an environment, (3) designing lessons, (4) understanding and accepting diversity, (5) conducting authentic assessments, and (6) exploring oneself to foster individual aptitudes. Each step of this process enables learners to develop their skills and potentials comprehensively to meet current challenges and demands effectively, and sustainably.